Perjuangan Perempuan dalam Novel Para Pawestri Pejuang Karya Suparto Brata dan Novel Gods Callgirl Karya Carla Van Raay (Kajian Sastra Bandingan) - Farahanna Juliani (Universitas Negeri Surabaya, 2019)
Para Pawestri Pejuang by Suparto Brata and God's Callgirl by Carla Van Raay have a woman struggle similarities form. The novels will be dissected using the liberal feminist theory by Naomi Wolf and comparative literature study of affinity by Suripan Sadi Hutomo. The focus of this research is to know how form of womans role and position in the economys field, womans aspiration delivery and womans life after married. The purpose of this research is to know womans role and position in the economys field, womans aspirations delivery and womans life after married. The result of the research stated that the novels have different economic struggles form, woman aspirations delivery, and womans life after married because they have different cultural, Javanese and Australian culture. The method in this research is qualitative descriptive, the research instrument is the researcher itself, data collection techniques is library techniques, data analysis techniques is descriptive techniques, and using time triangulation techniques for testing techniques of data validity. Keywords: role, position, feminism, comparative literature